Opinion on the question: with which bases of reason and right gender ideology is inserted and forced in politics, church and schools? - Slenczka, Reinhard; Sell, Ingeborg (Vox Scripturae - Revista Teológica Internacional, 2017)
The present text constitutes a theological opinion on the ideology of gender. After defining the concept of gendermainstreaming, the author demonstrates that there are no legal, scientific or theological bases for the forced introduction of gender ideology into politics, in schools and in churches. The article presupposes the social, legal and ecclesiastical context of Germany.